Osseointegration of zirconia dental implants modified by femtosecond laser vs. zirconia implants in healed bone: a histomorphometric study in dogs with three-month follow-up - J.L. Calvo-Guirado; M.L. Ramos-Oltra; B. Negri; R.A. Delgado-Ruíz; P. Ramirez-Fernández; J.E. Mate-Sánchez; M. Abooud; J. Gargallo Albiol; M. Satorres Nieto; G. Romanos (Ariesdue, 2013)
Aim The aim of the present study was to evaluate the stability and osseointegration of zirconia dental implants modified by femtosecond laser vs. zirconia implants with sandblasted surface.Materials and methods A total of 48 dental implants were used in this study. After the extraction of premolars (P2, P3, P4) and molars (M1), and 2-months healing period, implants were randomly inserted in both sides of the lower jaw of 6 American Foxhound dogs: 16 zirconia implants with sandblasted surface on endosseous portion (Control Group), 16 zirconia implants with sandblasting and laser modification of the endosseous neck portion only (Test Group A), and 16 zirconia implants with sandblasting and laser modification over the whole endosseous portion (Test Group B). Stability was evaluated by Periotest, while osseointegration was evaluated by Bone-to-implant contact (BIC) assessed by histomorphometry at 1 and 3 months after surgery.Results All implants were stable; Periotest® values (PTV) for Control Group were -5.75 ± 0.22; for Group A -6.125 ± 0.26 and for Group B -7.625 ± 0.27. BIC was greater for group B implants at both 1 and 3 months. No differences between the Control Group and Group A over the examined time periods were detected.Conclusion The present results suggested that the surface treatment of zirconium implants by femtosecond laser increases implant stability and bone to implant contact.